ANALISIS FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PENYALURAN KREDIT BANK UMUM KONVENSIONAL DI INDONESIA - Verina Riska (2020)
This research is using quantitative study aimed to see wheter there the effect of Credit Risk, Liquidity, Inflation, and Exchange Rate on Credit Distribution. The population used in this study is the Conventional Commercial Bank, which numbered 40 companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2019. By using Slovin sampling method and obtained 36 banking companies with research period of four years to obtain 144 sample units. Data analysis was performed using Microsoft Excel 2013 and hypothesis testing in this study used panel data regression analysis with E-Views program 10.0 and a significant level 5%. The results of this study indicated that Liquidity as measured by Loan to Deposit Ratio (LDR) have a positive and significant effect on Credit Distribution, while Credit Risk as measured by Non Performance Loans (NPL), Inflation as measured by the average of IHK, and Exchange Rate as measured by median rate has not effect on Credit Distribution. Keywords : Credit Risk, Liquidity, Inflation, Exchange Rate, and Credit Distribution